(untitled) (Communications in Mathematical Research, 2021)
In this paper, we consider a predator-prey model. A sufficient condition is presented for the stability of the equilibrium, which is different from the one for the model with Hassell-Varley type functional response. Furthermore, by constructing a Lyapunov function, we prove that the positive equilibrium is asymptotically stable.